2017
DOI: 10.1016/j.cgh.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Chromoendoscopy for Surveillance in Ulcerative Colitis and Crohn’s Disease: A Systematic Review of Randomized Trials

Abstract: In surveillance of inflammatory bowel diseases, chromoendoscopy identifies more patients with dysplasia only when compared with standard-definition white-light endoscopy. It is associated with longer procedural time with no direct evidence of effect on preventing all-cause/cancer-specific mortality or time to interval cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
2
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 49 publications
1
49
2
16
Order By: Relevance
“…Two studies comparing the detection rate of CC/D by chromoendoscopy and by NBI concluded that the detection rate by NBI was slightly inferior to that by chromoendoscopy . These results are consistent with those of two previous meta‐analyses . SCENIC concluded, “When performing surveillance with standard‐definition, high‐definition and image‐enhanced high‐definition colonoscopy, narrow‐band imaging is not suggested in place of white‐light colonoscopy and chromoendoscopy.”…”
Section: Detection Of Cc/dsupporting
confidence: 89%
“…Two studies comparing the detection rate of CC/D by chromoendoscopy and by NBI concluded that the detection rate by NBI was slightly inferior to that by chromoendoscopy . These results are consistent with those of two previous meta‐analyses . SCENIC concluded, “When performing surveillance with standard‐definition, high‐definition and image‐enhanced high‐definition colonoscopy, narrow‐band imaging is not suggested in place of white‐light colonoscopy and chromoendoscopy.”…”
Section: Detection Of Cc/dsupporting
confidence: 89%
“…Bei Patienten mit Colitis ulcerosa [458 -462] oder HNPCC [463,464] ist eine höhere Detektionsrate neoplastischer Läsionen durch Chromoendoskopie wahrscheinlich, allerdings ohne bewiesenen Effekt auf den Gesamt-Outcome [462]. Es ist bisher nicht geklärt, ob die Erkennung höherer Raten vorwiegend kleiner Veränderungen dem Patienten nutzen und den erhöhten Zeitaufwand der direkten Chromoendoskopie rechtfertigen.…”
Section: Level Of Evidence 1bunclassified
“…Guideline recommendations supporting the use of chromoendoscopy are based on evidence from observational studies and randomised trials that have methodological limitations due to selection, performance, detection, attrition or reporting bias. In a recent systematic review of randomised trials, we found that chromoendoscopy identifies more patients with dysplasia only when compared to standard definition white‐light endoscopy, with no evidence of a difference in the comparison with high definition white‐light endoscopy, narrow band imaging and i‐SCAN …”
Section: Introductionmentioning
confidence: 91%
“…In a recent systematic review of randomised trials, we found that chromoendoscopy identifies more patients with dysplasia only when compared to standard definition white-light endoscopy, with no evidence of a difference in the comparison with high definition white-light endoscopy, narrow band imaging and i-SCAN. 15 Standard pairwise meta-analysis only allows the direct comparison of two endoscopic techniques that have been evaluated headto-head in randomised trials. In a setting in which there are severall options for endoscopic dysplasia surveillance, a network meta-analysis can facilitate comparisons of all endoscopic procedures simultaneously within a single framework and rank available techniques according to efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%